2002
DOI: 10.1089/10430340252837206
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Cell Loss Induced by Human A30P α-Synuclein Gene Transfer to the Rat Substantia Nigra

Abstract: Somatic cell gene transfer was used to express a mutant form of alpha-synuclein (alpha-syn) that is associated with Parkinson's disease (PD) in the rat substantia nigra (SN), a brain region that, in humans, degenerates during PD. DNA encoding the A30P mutant of human alpha-syn linked to familial PD was incorporated into an adeno-associated virus vector, which was injected into the adult rat midbrain. The cytomegalovirus/chicken beta-actin promoter was used to drive transgene expression. Over a 1-year time cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
157
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(170 citation statements)
references
References 33 publications
13
157
0
Order By: Relevance
“…In this respect, the choice of vector is critical. In agreement with other reports, [31][32][33][34] we have shown that an AAV2-based vector can maintain expression of the transgene and hence of the therapeutic protein for 41 year. In addition to the choice of vector, the choice of promoter is also critical for long-term high …”
Section: Durationsupporting
confidence: 93%
“…In this respect, the choice of vector is critical. In agreement with other reports, [31][32][33][34] we have shown that an AAV2-based vector can maintain expression of the transgene and hence of the therapeutic protein for 41 year. In addition to the choice of vector, the choice of promoter is also critical for long-term high …”
Section: Durationsupporting
confidence: 93%
“…GFP fluorescence was detected in cell bodies in the SN and in neurites in the corpus striatum of animals injected with the GFP vector. Co-localization studies showed that the GFP fluorescence overlapped with TH immunofluorescent labeling in the majority of dopaminergic neurons in the SN pars compacta as we observed previously (Klein et al, 2002a). Co-localization studies with an antibody against parvalbumin, a marker for GABAergic neurons, demonstrated efficient expression of GFP in parvalbumin neurons of the SN pars reticulata as well (not shown).…”
Section: Tau Gene Transfer To the Sn Causes Loss Of Pars Compacta Neusupporting
confidence: 79%
“…The ASN gene transfer also produced loss of TH immunoreactivity in the pars compacta (Fig. 3F) as we observed previously (Klein et al, 2002a).We evaluated the number of SN pars compacta dopaminergic neurons after tau gene transfer by unbiased stereology on sections immunostained for TH (Table 2). GFP gene transfer did not alter the number of dopaminergic neurons compared to uninjected tissues; however, the P301L vector did cause a significant loss of dopaminergic neurons relative to control GFP gene transfer (P < 0.001, one-way ANOVA/Bonferroni's multiple comparison test) at 4 months post-injection.…”
supporting
confidence: 72%
See 2 more Smart Citations